Effect of inoculation during different phases of agricultural waste composting on spectroscopic characteristics of humic acid - Huang, Hong-li; Zeng, Guang-ming; Luo, Lin; Zhang, Jia-chao; Yu, Man; Qin, Pu-feng (Journal of Central South University, 2015)
The white-rot fungus, Phanerochaete chrysosporium ( P. chrysosporium ), was inoculated during different phases of agricultural waste composting and its effect on the spectroscopic characterization of humic acid (HA) was studied. Three runs were used in this study: Run A was the control without inoculating, and Runs B and C were inoculated P. chrysosporium during the first and the second fermentation phase, respectively. The elemental analysis, ultra-violet spectroscopy (UV), fluorescence spectra, Fourier transform infra-red (FTIR) and 13 C nuclear magnetic resonance ( 13 C-NMR) of HA all lead to the same conclusion, that is, the degree of aromatization and polymerization of HA increases after 42 days composting. However, the inoculation during different phases presents different effects. P. chrysosporium increases the degree of aromatization and polymerization of HA when it is inoculated during the second fermentation phase, while it does not produce an obvious change on the humification degree of HA when it is inoculated during the first fermentation phase.